Enhancing Learning Motivation through Islamic-Based CTL: The Role of Arabic Language Teachers at MTs Daarusy Syifaa - Imam Muttaqin; Zahrodin Fanani (Walada: Journal of Primary Education, 2026)
This study aims to analyze the role of Arabic language teachers in enhancing students’ learning motivation through an Islamic-based Contextual Teaching and Learning (CTL) approach at MTs Daarusy Syifaa’ East Lombok. This research employed a qualitative descriptive design to explore in depth the learning process and the implementation of CTL Islami in a natural setting. Data were collected through observations, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing.The findings reveal that the implementation of CTL Islami creates a more active, meaningful, and student-centered learning environment. Teachers play a crucial role as facilitators, motivators, and role models by integrating contextual learning strategies such as inquiry, modeling, questioning, and reflection with Islamic values derived from the Qur’an and Hadith. This approach enables students to connect Arabic language materials with their daily experiences, thereby increasing their interest and engagement in learning.Furthermore, the study shows that CTL Islami significantly enhances both intrinsic and extrinsic motivation. Students demonstrate greater enthusiasm, participation, and responsibility in the learning process. In addition, this approach contributes to the development of students’ linguistic competence, reflective thinking, and spiritual awareness.This study concludes that the integration of contextual learning and Islamic values provides a holistic and effective approach to improving students’ motivation in Arabic language learning. Therefore, CTL Islami can be considered a strategic pedagogical approach for Islamic educational institutions, particularly madrasahs, in the digital era.